CONSTRUCTION OF A MATHEMATICAL MODEL OF THE10Е02 CONDENSER HEAT EXCHANGER FOR HEATING OIL AND GAS CONDENSATE RAW MATERIALS - Rakhimjanova Shakhnoza Saidanvarovna; Khudayberdiev Absalom Abdurasulovich; Sheralieva Ozoda Anvarovna; Akhmedov Mansur Eshmamatovich; Shamadinova Nargis Erkinovna; Atamuratova Malohat Shovkatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Ensuring energy efficiency and energy conservation is one of the most important factors for the successful implementation of the economic and social reforms being carried out in our country. The intensification of the problem associated with the constant increase in the cost of energy carriers leads to finding ways to reduce consumption costs and efficient use of energy resources. Finding the optimal modes of production and consumption of energy, organizing its accounting. When solving a set of technical measures to increase the efficiency of the atmospheric oil distillation unit of the Bukhara Oil Refinery, a system of mathematical equations has been developed. It allows determining the optimal technological cost of oil and gas condensate of raw materials, while reducing the existing heat transfer surface of heat exchange equipment in production and reducing the consumption of heat and electricity. Based on thermal, technical, and economic calculations, it is shown that the proposed method helps to reduce the consumption of energy costs.